Association between Cystatin C, CRP in patients of Diabetic Nephropathy with Type 2 Diabetes Mellitus - Qurat Ul Ain, R. Zahid Butt, Saba Bari, Urwa Sarwar, W Ullah Khan, S. T. Naseem, M. Z. Anwar, A.U. Haq, G. Hussain, T. Laique, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Both developed and developing countries are facing the threat of end stage renal disease mainly caused by diabetes mellitus type 2. Aim: To see an association between levels of Cystatin C and CRP in diabetic nephropathy patients. Study design: Randomized controlled trial. Methodology: A total of 285 patients confirmed Type 2 diabetes mellitus were inducted in study. Patients were subjected to standard interview questionnaire regarding age, duration and complications of diabetes. High sensitive latex enhanced immunoturbidimetric method was used to measure the serum levels of Cystatin C and CRP. High density lipoproteins (HDL), Low density lipoprotein (LDL), total cholesterol and glycosylated Hemoglobin (HBA1C) levels were also measured and interpreted. Doppler ultrasound was performed for structural evaluation of renal functions. SPSS 25.0 was used to analyze the whole data. The difference between all the groups was analyzed using One-Way Analysis of Variance (ANOVA). Results: There was no statically Significant difference among age, sex, blood pressure, HDL, LDL, TC, and HBA1C levels among patients of all 3 groups, whereas CRP and Cystatin C levels were found to be raised with patients of moderate to severe nephropathy. Conclusion: It was concluded that albumin to creatinine ratio (ACR), serum Cystatin C and CRP are potential biomarkers of disease progression in patients with diabetic nephropathy.